Online Dispute Resolution Sebagai Alternatif Penyelesaian Sengketa Fintech Di Era IndustrI 4.0 - Waluyo; M. Kenza Radhya E. A.; Ersya Dwi Nurifanti (UNIVERSITAS PGRI YOGYAKARTA, 2023)
Abstract ODR offers a very broad scope of dispute or conflict resolution. Forms of disputes that are difficult to resolve through a settlement system in the real world, through ODR will be able to be resolved properly. It is known that the forms of disputes that arise include disputes over data protection, taxation, in transactions, and defamation or violation of privacy. The implementation of dispute resolution through ODR has basically been regulated in the regulations and procedures for providing dispute resolution services by each Alternative Dispute Resolution. Keywords: Financial Technology, ODR, LAPS.